Critical Analysis of Customary Law and Community Welfare - Judy Marria Saimima; Hadibah Zachra Wadjo; Harly Clifford Jonas Salmon (Journal of Adat Recht, 2025)
This study aims to critically analyze the role of customary law in improving community welfare, as well as how customary law is accommodated or confronted with the national legal system in the context of development. The method used is the Systematic Literature Review (SLR), which allows researchers to compile and synthesize information from various academic sources systematically, structured, and critically. The research process begins with the formulation of research questions, literature selection based on inclusion and exclusion criteria, evaluation of source quality, to narrative synthesis of the main themes that emerge from the literature, such as customary-based natural resource management, protection of local community rights, and state recognition of customary law. The results of the study show that customary law, as an unwritten legal system that is flexible and contextual, plays an important role in maintaining cultural identity, resolving conflicts, and managing resources sustainably. Although recognized in the constitution, customary law faces external challenges such as modernization and pressure from state law, as well as internal challenges such as potential discrimination and cultural commodification. Therefore, it is necessary to update customary law to be more inclusive and adaptive, as well as harmonious integration with national law supported by government policies, customary leaders, and civil society. This study emphasizes the importance of strengthening customary law as a strategic element in realizing the welfare of indigenous communities in a just and sustainable manner.